A Comparison of Minimally Invasive and Open Transforaminal Lumbar Interbody Fusion for Grade 1 Degenerative Lumbar Spondylolisthesis: An Analysis of the Prospective Quality Outcomes Database. Issue 3 (14th May 2020) - Chan, Andrew K; Bisson, Erica F; Bydon, Mohamad; Foley, Kevin T; Glassman, Steven D; Shaffrey, Christopher I; Wang, Michael Y; Park, Paul; Potts, Eric A; Shaffrey, Mark E; Coric, Domagoj; Knightly, John J; et al.
ABSTRACT: BACKGROUND: It remains unclear if minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) is comparable to traditional, open TLIF because of the limitations of the prior small-sample-size, single-center studies reporting comparative effectiveness. OBJECTIVE: To compare MI-TLIF to traditional, open TLIF for grade 1 degenerative lumbar spondylolisthesis in the largest study to date by sample size. METHODS: We utilized the prospective Quality Outcomes Database registry and queried patients with grade 1 degenerative lumbar spondylolisthesis who underwent single-segment surgery with MI- or open TLIF methods. Outcomes were compared 24 mo postoperatively. RESULTS: A total of 297 patients were included: 72 (24.2%) MI-TLIF and 225 (75.8%) open TLIF. MI-TLIF surgeries had lower mean body mass indexes (29.5 ± 5.1 vs 31.3 ± 7.0, P  = .0497) and more worker's compensation cases (11.1% vs 1.3%, P  < .001) but were otherwise similar. MI-TLIF had less blood loss (108.8 ± 85.6 vs 299.6 ± 242.2 mL, P  < .001), longer operations (228.2 ± 111.5 vs 189.6 ± 66.5 min, P  < .001), and a higher return-to-work (RTW) rate (100% vs 80%, P  = .02). Both cohorts improved significantly from baseline for 24-mo Oswestry Disability Index (ODI), Numeric Rating Scale back pain (NRS-BP), NRS leg pain (NRS-LP), and Euro-Qol-5 dimension (EQ-5D) ( P  > .001). In multivariable adjusted analyses, MI-TLIF was associated with lower ODI (β = −4.7; 95% CI = −9.3 to −0.04; P  = .048), higher EQ-5D (β = 0.06; 95% CI = 0.01-0.11; P  = .02), and higher satisfaction (odds ratio for North American Spine Society [NASS] 1/2 = 3.9; 95% CI = 1.4-14.3; P  = .02). Though trends favoring MI-TLIF were evident for NRS-BP ( P  = .06), NRS-LP ( P  = .07), and reoperation rate ( P  = .13), these results did not reach statistical significance. CONCLUSION: For single-level grade 1 degenerative lumbar spondylolisthesis, MI-TLIF was associated with less disability, higher quality of life, and higher patient satisfaction compared with traditional, open TLIF. MI-TLIF was associated with higher rates of RTW, less blood loss, but longer operative times. Though we utilized multivariable adjusted analyses, these findings may be susceptible to selection bias.